2020
DOI: 10.15244/pjoes/111883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Progressive Overload Changes of the Musculoskeletal System in Automobile Industry Workers

Abstract: The formation of overload changes is a well-known concept. Numerous factors contributing to the development of progressive overload changes have also been described, including stress, performing repetitive movements, non-physiological working position, etc. [2][3][4]. Production line workers constitute an occupational group that is exposed to many of the above-mentioned risk factors. Therefore, the aim of our study is to establish the most common types of musculoskeletal overloads and to investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…All procedures were conducted according to the 1964 Declaration of Helsinki. All subjects filled in a questionnaire ( Błaszczyk et al, 2020 ) and reported musculoskeletal pain, especially in the lumbar spine ( Table 2 ). The seniority of each subject at a particular position was at least 5 years ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All procedures were conducted according to the 1964 Declaration of Helsinki. All subjects filled in a questionnaire ( Błaszczyk et al, 2020 ) and reported musculoskeletal pain, especially in the lumbar spine ( Table 2 ). The seniority of each subject at a particular position was at least 5 years ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Signals from the following 5 muscles were recorded bilaterally: erector spinae (ES), latissimus dorsi (LD), lower trapezius (LT), middle deltoideus (MD) and pectoralis major (PM). The examined muscles were identified in a pilot study based on a survey ( Błaszczyk et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Muscular imbalances are largely caused by one-sided loads and non-physiological posture patterns as well as sedentary lifestyles and obesity [10,11]. If physical activity and weight reduction can also lead to an improvement in the pain situation what has been demonstrated earlier [12,13], non-physiological stress and posture patterns are often due to occupational activities which, due to the specific occupational requirements, can often not or only partially be corrected [14][15][16][17][18].…”
Section: Objectivementioning
confidence: 99%